Aplikasi Arsitektur Modern Pada Redesain Pasar Induk Tradisional Lambaro - Rudy Saputra (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2020)
The trade sector is the most important thing in a district, especially the Lambaro Traditional Market which became the main driver of the economy in the area. But, the current condition of the market looks very chaotic, slum, dirty due to lack of maintenance, both in physical buildings and facilities, so that it’s necessary to do a redesign of the market in order to be able to compete with modern markets that are developing at this time.. Application of the theme for market redesignis "Modern Architecture", this is because the theme has an architectural style that offers simplicity (not excessive) and functional. Modern architecture can be seen from the shape of the building mass that combined with the concept of metaphor, as well as the use of facilities that support for easy access of users. While the traditional concept is illustrated by the conditions and atmosphere of the market and the buying and selling transaction systems that still applies with tradition of bargaining between sellers and buyers. This design also refers to the type A of market criteria regulation issued by the government and the Indonesian ministry.